Re-evaluation of Pasteuria ramosa Metchnikoff 1888, a Bacterium Pathogenic for Daphnia Species - HIRSCH, PETER (International Journal of Systematic and Evolutionary Microbiology, 1972)
Recent examination of Daphnia spp. collected from Lake Erie and several locations in southern Michigan, U.S.A., revealed the presence of structures that resembled those described by Metchnikoff in 1888 as stages of the life cycle of Pasteuria ramosa. Flat, elongated forms from the body cavity near the joints of extremities resembled, especially when aggregated in the form of rosettes, bundles of flat crystals rather than stages of a microorganism. Spherical or pear-shaped bodies with buds were found aggregated on the surface or inside of antennae and other extremities. Similarity of these bodies with certain budding bacteria is suggested, and it is proposed to retain the original name P. ramosa Metchnikoff but to restrict it to these budding forms only. The longitudinal fission attributed to this bacterium is dubious and may have resulted from misunderstanding crystal-like structures for microorganisms.